2021
DOI: 10.3389/fnins.2021.683298
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Pulsed-Radiofrequency Combined With Transforaminal Epidural Steroid Injection for Lumbosacral Radicular Pain Caused by Distinct Etiology

Abstract: BackgroundLumbosacral radicular pain (LSRP) can be caused by disc herniation, spinal stenosis, and failed back surgery syndrome. The clinical effect of pulsed-radiofrequency (PRF) combined with transforaminal epidural steroid injection (TESI) for radiating pain in different population remains unclear.MethodsWe retrospectively reviewed the medical recordings of patients with LSRP caused by different etiologies, who underwent PRF and TESI treatment. The primary clinical outcome was assessed by a 10-point Visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…In our study, the pain duration of all patients was ≥ 2 years (the mean duration of 4 years), which was notably longer than that in previous studies, in which the means of pain duration were about one year ( Chang et al, 2017 ; Lee et al, 2018 ). The successful pain relief rate in our study was higher than that in the previous study (80 vs. 76%, 80 vs. 52.2%) ( Chang et al, 2017 ; Lee et al, 2018 ), which might be related to the differences including patient selections, combined treatments (combining TFESI and PRF) (Karaköse Çalışkan et al, 2021; Yang et al, 2021 ), and multilevel strategy. Well, the successful treatment rate in our study was similar to that in Lee’s study (80 vs. 81.8%), which used bipolar PRF to treat refractory chronic cervical radicular pain ( Lee et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In our study, the pain duration of all patients was ≥ 2 years (the mean duration of 4 years), which was notably longer than that in previous studies, in which the means of pain duration were about one year ( Chang et al, 2017 ; Lee et al, 2018 ). The successful pain relief rate in our study was higher than that in the previous study (80 vs. 76%, 80 vs. 52.2%) ( Chang et al, 2017 ; Lee et al, 2018 ), which might be related to the differences including patient selections, combined treatments (combining TFESI and PRF) (Karaköse Çalışkan et al, 2021; Yang et al, 2021 ), and multilevel strategy. Well, the successful treatment rate in our study was similar to that in Lee’s study (80 vs. 81.8%), which used bipolar PRF to treat refractory chronic cervical radicular pain ( Lee et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 73%
“…Transforaminal epidural steroid injection (TFESI) is one of the most common interventional options for the treatment of LDH ( Manchikanti et al, 2016 ) and several previous studies have demonstrated positive short-term effects of TFESI in reducing lumbar radicular pain ( Olguner et al, 2020 ; Oliveira et al, 2020 ), and TFESI combined with dorsal root ganglion pulsed radiofrequency (PRF) can be used to treat some complex and intractable LSRP ( Karaköse Çalışkan et al, 2021 ; Yang et al, 2021 ). In addition, the preoperative duration of pain can have a significant impact on the outcomes after interventional treatments ( Munjupong and Kumnerddee, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the management of the demyelinating neuropathy is totally different from cervical spinal spondylosis. In this case, we applied percutaneous discectomy for cervical disc herniation, which is consistent with treatment of radiculopathy for decompression of nerve root [ 9 ]. Symptomatic relief after decompression therapy may also indicate the potential role of cervical nerve branch in persistent hiccup conditions.…”
Section: Discussionmentioning
confidence: 99%
“…About 80% of patients with chronic cervical radicular pain who have failed to respond to repeated treatment have reduced pain by more than 50% after ultrasound-guided bipolar PRF [10]. Bipolar PRF has better therapeutic effect than unipolar PRF, probably because bipolar PRF has stronger electromagnetic field and can cover the target more fully and accurately [11]. In a prospective randomized study, 60 V PRF was applied to patients the high-voltage group and 45 V PRF was applied to patients in the low-voltage group.…”
Section: Radicular Painmentioning
confidence: 99%